Criminal Justice Diversion and Liaison Services: A Path to Success?. Issue 1 (8th May 2012) - Dyer, Wendy
Abstract : Diversion services for adult mentally disordered offenders are back in the limelight twenty years after their original development. This article argues there are a number of important lessons to be learnt. Services of this kind 'process' different people in different ways with different outcomes. Current developments therefore need to provide an holistic, patient-centred approach across the whole offender pathway, which meets the needs of different groups of people. What works for some might not work for others, but patterns can be mapped and good and bad pathways identified and used to inform good practice and service improvement.